Privacy-aware enhanced homomorphic mechanism for group data sharing - Karemallaiah, Jayalakshmi; Revaiah, Prabha (Institute of Advanced Engineering and Science, 2025)
Cloud-based group data sharing has gained huge popularity in recent years. Accomplishing the efficacy and security of the data in a cloud-computing framework is challenging. Sharing data in a cloud environment is quite challenging and needs to be resolved. Furthermore, while exchanging data on the cloud, it is challenging to achieve both anonymity and traceability. The main aim of this research work is to make it easier for the same group to share and store anonymous data on the cloud securely and effectively. This research work presents verifiable privacy-aware enhanced homomorphic (VPEH) encryption for multiple participants; moreover, the enhanced homomorphic encryption mechanism provides end-to-end encryption and allows the secure computation of data without revealing any data in the cloud. The proposed algorithm uses homomorphic multiplication to compute the hashes product of challenges blocks that makes it more efficient Furthermore, an additional security model is incorporated to verify the shared data integrity. The VPEH mechanism is evaluated considering parameters such as tag generation, proof generation, and verification; model efficiency is proved by observing the marginal improvisation over the other existing model by varying the number of blocks and several challenge blocks.